Developing Environmental Numeracy Materials through Problem-Based Learning and Contextual Mathematics for Young Learners - Delamontano, Eldo; Endyana, Cipta; Winoto, Yunus; Novianti, Evi (Mimbar Sekolah Dasar, 2025)
This study develops and examines an educational material that integrates mathematics learning with environmental awareness, titled Mathematics in Action: Counting Waste, Saving the Earth. Designed for learners aged 8 to 12, the material connects core arithmetic concepts such as addition, multiplication, and estimation with real-world environmental issues, particularly waste management. Using authentic local data from the Citarum River in West Java as a contextual anchor, students engage in mathematical activities that encourage reflection on personal consumption habits and the long-term ecological impact of daily behavior. Employing a descriptive qualitative design that combines a systematic literature review and semi-structured interviews with mathematics teachers, the study synthesizes key perspectives from Environmental Education, Contextual Mathematics, and Problem-Based Learning. The findings indicate that embedding mathematics within environmental contexts enhances student engagement, critical thinking, and emotional connection to sustainability issues. Furthermore, the material aligns with Sustainable Development Goal 12 (Responsible Consumption and Production), offering a practical and values-driven model for integrating ecological literacy into elementary mathematics curricula. This research contributes to the broader discourse on interdisciplinary education and demonstrates how foundational math skills can foster environmental responsibility from an early age.